Revisiting the matching function - Britta Kohlbrecher; Christian Merkl; Daniela Nordmeier (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2014)
Many labor market models use both idiosyncratic productivity and a vacancy free entry condition. This paper shows that these two features combined generate an equilibrium comovement between matches on the one hand and unemployment and vacancies on the other hand, which is observationally equivalent to a constant return Cobb-Douglas function commonly used to model match formation. We use German administrative labor market data to show that the matching function correlation solely based on idiosyncratic productivity and free entry is very close to the empirical matching function. Consequently, we argue that standard matching function estimations are seriously biased if idiosyncratic productivity plays a role for match formation. In this case, they are not suitable for the calibration of labor market models. – – Das Papier zeigt, dass das Verhältnis zwischen neugeschaffenen Stellen auf der einen Seite und Arbeitslosigkeit und Vakanzen auf der anderen Seite ('Matching-Funktion') durch eine Kombination aus idiosynkratischen Produktivitätsschocks und freiem Markteintritt von Vakanzen getrieben werden kann. Die Analyse mit deutschen administrativen Arbeitsmarktdaten ergibt, dass ein großer Teil des Zusammenhangs von Einstellungsrate und Arbeitsmarktanspannung über idiosynkratische Schocks verursacht wird. Dies impliziert, dass Schätzungen der Matching-Funktion nur bedingt geeignet sind, um Arbeitsmarktmodelle zu kalibrieren.
Keywords: E24; E32; J63; J64; 330; matching function; idiosyncratic productivity; job creation; vacancies